2018
DOI: 10.1039/c7se00389g
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring oxygen redox reactions in ionic liquid based Li/O2 batteries by means of the Li+ dopant concentration

Abstract: a Ionic liquids' (ILs) reusability, non-volatility and non-corrosiveness, as well as their ease of isolation and a large electrochemical stability window make them an interesting choice as environment-friendly electrolyte for metal/air batteries. ILs have been described as designer solvents as their properties and behaviour can be adjusted to suit an individual reaction need. In the framework of this study we applied a conceptually similar designer approach and show that a simple parameter as the concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…In effect, we have shown that the discharge mechanism and the consequent morphology of the deposits is a major factor to consider before determining an optimal electrode architecture [11]. Factors like current density [12,13,14,15,16], electrolyte [17,18,19,20], and cell design [11] can significantly determine whether a surface Li 2 O 2 film forms or larger particles grow from the solution phase. When a 5–10 nm film forms, the ideal pore diameter is twice this thickness, for which pores between 20–40 nm are optimal [21].…”
Section: Introductionmentioning
confidence: 99%
“…In effect, we have shown that the discharge mechanism and the consequent morphology of the deposits is a major factor to consider before determining an optimal electrode architecture [11]. Factors like current density [12,13,14,15,16], electrolyte [17,18,19,20], and cell design [11] can significantly determine whether a surface Li 2 O 2 film forms or larger particles grow from the solution phase. When a 5–10 nm film forms, the ideal pore diameter is twice this thickness, for which pores between 20–40 nm are optimal [21].…”
Section: Introductionmentioning
confidence: 99%
“…40 Moreover, by adjusting the Li + concentration and the temperature of the ionic liquid electrolytes, the surfacemediated Li 2 O 2 growth mechanism can be transformed into the solution-phase, thereby improving the cycle stability of the lithium-oxygen batteries. 41,42 In this work, using the non-solvent-induced phase separation (NIPS) method, we prepared a PEI-based polymer separator with high porosity, high thermal and chemical stability. During the separator formation process, the in-situ hydrolysis reaction of tetrabutyl titanate (TBT) can not only precisely control the pore structure of the PEI-based polymer separator, but also realize the uniform dispersion of nano-TiO 2 in the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%